Layanan Dukungan Psikososial (LDP) Untuk Mengurangi Trauma Pasca Bencana - Yeni Agustin; Diana Tria Jaeni Noer; Kemal Fajar Pratama; Isti Isiya; Gita Istiqomatul Hayati; Fitri Arnita (CV. Lentera Literasi Indonesia, 2026)
Indonesia is a country prone to natural disasters that cause not only physical damage but also profound psychological trauma to survivors. Often, disaster management focuses more on physical infrastructure reconstruction, neglecting the emotional healing or mental health of victims. This study aims to examine the effectiveness and approach of Psychosocial Support Services (PSS) in reducing post-disaster trauma. The method used is a literature review by analyzing 10 relevant scientific articles published in the last five years (2020–2025) obtained through Google Scholar. The results of the study show that PSS plays a vital role as a protective factor in preventing long-term psychological effects. Various intervention methods such as Psychological First Aid (PFA), play therapy, and community-based approaches have been proven effective in reducing anxiety, stress, and trauma symptoms, especially in vulnerable groups such as children and adolescents. In addition, PSS contributes to increasing resilience and restoring social functioning in the community. This study concludes that synergy between volunteer readiness, community support, and government policies is essential to achieve holistic disaster management.